Forming electorates, forging spaces - Flint, Colin (1998)
Using a social constructivist view of space, the agency of both the Nazi Party and the electorate created spatial contexts that, in turn, mediated future political activity. Spatial statistical analysis of aggregate voting data models the diffusion of Nazi Party electoral support across space as well as the construction of regionally specific electorates. The statistical concept of spatial dependence captures the creation of new spaces of power by the Nazi Party. The concept of spatial heterogeneity captures how the Nazi Party's electorate was composed of different socioeconomic groups in different regional settings. The growth of the Nazi party vote in Baden between May 1924 and July 1932 is used to exemplify the social theoretical view of space and the application of spatial statistics. - Reproduced
Keywords: Political parties - Germany; Nazi party; Elections - Germany; Elections